The impact of EFD on VAT collection in Tanzania: The case of Morogoro council - Swallo, Bahati Gregory (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirement for the award of the Degree of Masters of Business Administration in Corporate Management(MBA-CM) of Mzumbe University